A SIMPLE AND SEAMLESS VERTICAL HAN DOFF PROTOCOL TO ENHANCE THE PERFORMANCE OF DATA SERVICES IN INTEGRATED UMTS/WLAN NETWORK - RIZVI, SYED SAFDAR ALI (2014)
The Next Generation Wireless Network (NGWN) is speculated to be a unified network composed of several existing wireless access networks such as Wireless Local Area Network (WLAN). Global System for Mobile (GSM). Universal Mobile Telecommunications System (UMTS). Worldwide lnteroperability for Microwave Access (WiMAX). and satellite network etc. The NGWN will permit the wireless client to roam across diverse integrated access networks while maintaining the session continuity. In order to maintain the session continuity in such an internetworking environment, the most important and challenging issue is to attain the seamless mobility. The literature demonstrated that when the wireless client switches the active data session between the heterogeneous wireless access networks, the loose coupling based mobility management techniques lack in providing the seamless mobility.